Amblyomma parvitarsum (Acari: Ixodidae): localities, hosts and host-parasite ecology - Muñoz-Leal, Sebastian (2014)
Only a few aspects of the biology of Amblyomma parvitarsum Neumann are known. Adults of this hard tick species are parasites of South American camelids in the Andean plateau of Argentina, Bolivia, Peru and Chile and also in the Argentine Patagonia, but they have been also rarely found on other artyodactils and two species of birds. The larva has been collected from reptiles in northern Chile, whereas the hosts for the nymph remain unknown. On nine localities included within Altitude Tropical and Perarid Mediterranean ecoregions in northern Chile, we analyzed 237 reptiles, 285 birds, 624 rodents and 52 camelids for infestation with A. parvitarsum to calculate seasonal prevalence of this tick. We also reviewed the literature of this tick and three entomological collections for obtaining and summarizing all the information to date about this tick. None of the analyzed birds and rodents were parasitized with A. parvitarsum; however, seven over a total of ten reptile species that we caught were infested with the larva. In the camelid species Lama glama and Vicugna pacos we collected adult specimens of this tick. Larval prevalence was higher during fall (75 %) in Liolaemus pleopholis in the Altitude Tropical ecoregion. We also collected adult specimens of A. parvitarsum from camelid manure heaps during summer in Salar de Surire and Llullaillaco localities. Additionally, we also reviewed the literature of this tick and examined specimens in three entomological collections for obtaining and summarizing all the information to date about this tick. By this study, nine localities and seven new hosts are added for A. parvitarsum and we confirm reptiles as specific hosts of this tick larva.